Titin and desmosomal genes in the natural history of arrhythmogenic right ventricular cardiomyopathy. Issue 10 (25th August 2014) - Brun, Francesca; Barnes, Carl V; Sinagra, Gianfranco; Slavov, Dobromir; Barbati, Giulia; Zhu, Xiao; Graw, Sharon L; Spezzacatene, Anita; Pinamonti, Bruno; Merlo, Marco; Salcedo, Ernesto E; Sauer, William H; et al.
Abstract : Background: Genotype–phenotype correlations are poorly characterised in arrhythmogenic right ventricular cardiomyopathy (ARVC). We investigated whether carriers of rare variants in desmosomal genes (DC) and titin gene ( TTN ) display different phenotypes and clinical outcomes compared with non-carriers (NT-ND). Methods and results: Thirty-nine ARVC families (173 subjects, 67 affected) with extensive follow-up (mean 9 years), prospectively enrolled in the International Familial Cardiomyopathy Registry since 1991, were screened for rare variants in TTN and desmosomal genes ( DSP, PKP2, DSG2, DSC2 ). Multiple clinical and outcome variables were compared between three genetic groups ( TTN, DC, NT-ND) to define genotype–phenotype associations. Of the 39 ARVC families, 13% (5/39) carried TTN rare variants (11 affected subjects), 13% (5/39) DC (8 affected), while 74% (29/39) were NT-ND (48 affected). When compared with NT-ND, DC had a higher prevalence of inverted T waves in V2-3 (75% vs 31%, p=0.004), while TTN had more supraventricular arrhythmias (46% vs 13%, p=0.013) and conduction disease (64% vs 6% p<0.001). When compared with the NT-ND group, the DC group experienced a worse prognosis (67% vs 11%, p=0.03) and exhibited a lower survival free from death or heart transplant (59% vs 95% at 30 years, and 31% vs 89% at 50 years, HR 9.66, p=0.006), while the TTN group showed an intermediate survival curve (HR 4.26, p=0.037). Conclusions: TTN carriers display distinct phenotypic characteristics including a greater risk for supraventricular arrhythmias and conduction disease. Conversely, DC are characterised by negative T waves in anterior leads, severe prognosis, high mortality and morbidity.